Parathyroid Carcinoma: An Up-to-Date Retrospective Multicentric Analysis. (6th March 2020) - Quaglino, Francesco; Manfrino, Luca; Cestino, Luca; Giusti, Massimo; Mazza, Enrico; Piovesan, Alessandro; Palestini, Nicola; Lauro, Corrado; Castellano, Elena
Abstract : Parathyroid carcinoma (PC) is a rare disease responsible for about 1% of primary hyperparathyroidism (PHPT) cases. PC usually has an indolent course, tough to differentiate from the benign causes of PHPT, and the only certain diagnosis is histologic. The gold standard surgical treatment is the en bloc resection associated with the homolateral thyroid loboistmectomy. The aim of this study was to underline the main differences between PC and benign PHPT, along with gathering epidemiological knowledge relative to PC in our region. Data from the regional cancer network (Rete Oncologica del Piemonte e della Valle d'Aosta) since 2007 have been reported, including 21 patients from three hospitals (AO S. Croce e Carle of Cuneo, AOU Città della Salute of Turin, and ASL Città di Torino). The incidence of the disease, gender, age at time of diagnosis, presence of renal and bone symptoms, serum calcium and PTH levels, surgical technique performed, and percentage of recurrence were analysed. PC data were than compared with a series of patients affected by benign PHPT, referred to ASL Città di Torino, Maria Vittoria Hospital, from 2007 to 2019. A PC incidence of 0.05 cases per 100, 000 inhabitants was found in our region. Benign forms occurred more frequently in females (p = 0.0002 ), while PC equally occurred in males and females and affected younger patients (p = 0.026 ). Serum calcium and PTH levels were significantly higher in PC patients; accordingly, typical PHPT symptoms were more frequently reported in PC than in benign PHPT. In the PC group, the en bloc resection shows a 13 times lower risk for relapse compared with all the other surgical techniques. PC is equally gender distributed, and the average patients' age is in the fifth decade of life. It is usually functioning, with greater biochemical activity and multiple symptoms. A not-radical surgical resection is associated with a higher recurrence rate. A meticulous presurgical evaluation of PHPT patients showing PC's evocative features is mandatory to obtain a complete disease extirpation.